Cardiac Sarcoidosis as an Uncommon Etiology for Posterior Circulation Stroke Presenting with Alexia without Agraphia - Mohankumar Kurukumbi; Lauren Gardiner; Shevani Sahai; John W. Cochran (Case Reports in Neurological Medicine)
Sarcoidosis is a systemic disease with cardiac involvement occurring in 20-50% of cases. Cardiogenic stroke caused by cardiac sarcoidosis, especially PCA infarction, is a rare clinical presentation that necessitates timely diagnosis and may warrant treatment prophylaxis against CVA. In this case report, we describe a 54-year-old Caucasian male presenting with left PCA stroke in the setting of cardiac and pulmonary sarcoidosis, and hypertension. His presenting symptoms included right partial hemianopia, difficulty with naming, memory, and recall, and alexia without agraphia. Cardiogenic stroke is an uncommon manifestation of cardiac sarcoidosis, and given the disabling nature of these sequelae, the importance of early diagnosis and prevention with anticoagulation is crucial to prevent morbidity and mortality.